TensorFlow Deep Learning Projects : 10 real-world projects on computer vision, machine translation, chatbots, and reinforcement learning /: 10 real-world projects on computer vision, machine translation, chatbots, and reinforcement learning. (2018) - Grigorev, Alexey; shanmugamani, rajalingappaa; Boschetti, Alberto; Massaron, Luca; Thakur, Abhishek
No abstract available